(untitled) (Biological Sciences - PJSIR, 2025)
The current COVID-19 outbreak poses the most significant global threat with unknown long- term and short-term consequences on the economy, public health and related healthcare sectors. SARS- CoV-2 is highly infectious and controlled measures in distancing socially and through sterilization must be sustained to neutralize the viral load especially in high risk areas. Now, the world is facing a new threat in the form of a novel Omicron variant of COVID-19 recently detected in Britain which was found to link to travel to southern Africa and was initially named B.1.1.529. This newly identified variant, a highly mutated variant that might be able to escape from vaccines was first identified in Botswana. This comprehensive review will provide the pathophysiological basis of coronavirus, vaccination status, virus strain variation and molecular basis of a virus to shed a detailed spread of the omicron strain that poses a global threat. The virulent nature of the virus and the emergence of new deadly strains led to the development of therapeutic strategies by understanding the pathogenesis of SARS-CoV-2. Globally, therapeutic management strategies are needed as they provide crucial knowledge for developing rapid diagnostics and treatment options that serve as major interventions for infection control management.